2008
DOI: 10.1902/jop.2008.070388
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Herpesviruses and Periodontal Pathogens in Subgingival Plaque of Patients With Chronic Periodontitis, Generalized Aggressive Periodontitis, or Gingivitis

Abstract: In Brazilian patients, HSV-1 and EBV-1, rather than HCMV, were more frequently associated with CP and AgP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
98
1
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(111 citation statements)
references
References 51 publications
7
98
1
5
Order By: Relevance
“…7,18,19 Although few studies showed similar detection rates of HCMV as in our study, there has been a wide and varied report with high levels of viruses to none in certain population with healthy periodontium. 7,9,17,18,[20][21][22][23] In CP, there have been varied reports with some studies finding very high levels of EBV and HCMV. 10,18,20,21,23 Our results showed significantly higher levels of both the HCMV and the EBV virus in CP as compared to the healthy periodontium but still was lower than the median range as quoted by Slots 2010.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7,18,19 Although few studies showed similar detection rates of HCMV as in our study, there has been a wide and varied report with high levels of viruses to none in certain population with healthy periodontium. 7,9,17,18,[20][21][22][23] In CP, there have been varied reports with some studies finding very high levels of EBV and HCMV. 10,18,20,21,23 Our results showed significantly higher levels of both the HCMV and the EBV virus in CP as compared to the healthy periodontium but still was lower than the median range as quoted by Slots 2010.…”
Section: Discussionmentioning
confidence: 99%
“…7,9,17,18,[20][21][22][23] In CP, there have been varied reports with some studies finding very high levels of EBV and HCMV. 10,18,20,21,23 Our results showed significantly higher levels of both the HCMV and the EBV virus in CP as compared to the healthy periodontium but still was lower than the median range as quoted by Slots 2010. 2 In his study, we noted that a co-infection of HCMV and EBV existed in CP group and this relationship was significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subgingival microflora in gingivitis represent a transition between that associated with health and periodontitis, 38 in which subgingival microflora shifts from being predominately gram-positive to an increased number of obligate anaerobic gram-negative organisms, such as Porphyromonas gingivalis, Tannerella forsythia, Treponema denticola, and Selenomonas noxia, as well as Campylobacter rectus, Aggregatibacter (formerly Actinobacillus) actinomycetemcomitans, and Prevotella intermedia, and spirochetes. [35][36][37][38][39][40][41] Other microorganisms found in PD include Chlamydophila pneumoniae 42 ; Mycoplasma 43,44 ; Helicobacter pylori [45][46][47] ; candida 48 -51 ; Epstein-Barr virus, cytomegalovirus, and herpesviruses [52][53][54] ; ameba 55 ; methane-producing microorganisms called archaea 56 -59 ; and sulfate-reducing bacteria and archaea. 60,61 Epithelium in the gingival sulcus interacts with bacteria in the subgingival crevicular space, generating and transmitting signals between bacteria and adjacent immune cells.…”
Section: Methanogenic Archaeamentioning
confidence: 99%
“…Herpes viruses may contribute to the pathogenesis of chronic and aggressive periodontitis (Table 4). There is speculation that Epstein-Barr virus-1 (EBV-1) and cytomegalovirus (CMV) may be involved in synergistic mechanisms with Aa, P. gingivalis and T. forsythia (Chalabi et al, 2010;Dawson et al, 2009;Imbronito et al, 2008;Slots 2010, Fritschi et al, 2008. Table 4.…”
Section: Plaque In Chronic Periodontitismentioning
confidence: 99%